Characteristics of Concrete With Red Sand Mixture 80 Mesh Grain Size After Combustion - Mukti Hamjah Harahap; Winsyahputra Ritonga; Nova Adelia (Postgraduate, University of Mataram, 2023)
Research has been done on the Characteristics of Concrete with a Mix of Red Sand Grain Size 80 Mesh Post-burning. This study aims to determine the characteristics of concrete with a mixture of red sand grain size 80 Mesh Post-burning on the compressive strength, porosity and structure of the concrete. The test object is a cube of 15 cm x 15 cm x 15 cm with concrete quality K-225. In this study, variations in the composition of 80 mesh size red sand were made of 0%, 2%, 3% and 4%. After the concrete is 24 hours old, the mold is opened and given a sample code and treated in an immersion water bath. After going through an immersion period of 28 days, the concrete was burned in an oven with temperature variations of 400℃, 550℃, 700℃ and 850℃ and tested. The test methods used are compressive strength, porosity and Scanning Electron Microscope Energy Dispersive X-Ray (SEM-EDX). From the test results obtained the maximum average compressive strength obtained in concrete with a mixture of red sand of 4% with a temperature of 550℃. From the results of the porosity test, there was a decrease in the concrete with the addition of red sand by 4%. From the results of the SEM test, the concrete structure with a mixture of red sand has fewer and smaller cavities. From the results of the EDX test on concrete with a mixture of red sand, Calcium (Ca) and Stibium (Sb) elements have increased intensity when compared to normal concrete. From the XRD test results obtained elements - elements SiO2 (Silicon Oxide), Ca(OH)2 (Calcium Hydroxide) and CaO3 (Calcite) with the highest intensity is SiO2.